Financial Markets and Corporate Finance 5th International Conference on FMCF (ICFMCF2023), IIT Delhi, India, July 6-8 - Singh, Shveta; Jain, Sonali (Springer Proceedings in Business and Economics, 2024)
IX, 350 p. 54 illus., 48 illus. in color.